Empowering rural communities: the role of financial literacy and management in sustainable development - Kyeyune, Gorrettie Nakyeyune; Ntayi, Joseph Mpeera (Frontiers in Human Dynamics, 2025)
Research problemIn the face of global efforts to combat poverty and enhance the well-being of vulnerable populations, aiming for inclusive growth, the 2024 UNDP trend report casts a shadow with its findings that the world remains off-course for achieving Sustainable Development Goal 1 (SDG1) “No Poverty.” Specifically, in Uganda, despite the integration of poverty eradication measures within national development agendas, the efficacy of such initiatives is critically contingent upon the financial literacy levels among the impoverished targets.AimThis study underscores the pivotal role of financial literacy in fostering the empowerment of underserved communities, directing them toward paths of inclusive growth.Research methodsAdopting a qualitative framework, this investigation spanned 7 parishes across five districts within Uganda’s Busoga region, selected via purposive sampling. Participants included a cross-section of community members—ranging from household heads and local entrepreneurs to SACCO (Savings and Credit Cooperative Organization) members and parish chiefs—all of whom engage with government-led poverty alleviation programs. A semi-structured interview guide facilitated the collection of nuanced data, which was subsequently transcribed and subjected to content analysis to distill key thematic insights.Results and discussionThe findings illuminate a stark reality: inadequate financial management and literacy significantly thwart the sustainable development of rural communities. Such deficiencies not only hamper economic progress but also stifle the potential for holistic community empowerment.ConclusionInvestment in financial literacy emerges as a crucial strategy, underscoring the importance of equipping individuals with the knowledge and skills necessary for economic participation and personal growth. This approach aligns with the principles of Amartya Sen’s Capability Approach and the Human Capital Theory, advocating for the prioritization of financial literacy initiatives within rural development strategies. The study accentuates the need for comprehensive financial literacy training, aimed at fulfilling broader policy objectives and catalyzing economic development and poverty reduction efforts.